State-of-the-art controlled low-strength materials using incineration industrial by-products as cementitious materials. (22nd August 2022) - Liu, Yiliang; Mo, Zongyun; Su, Youpo; Chen, Yanhua
Highlights: Sources and general situation of incineration industrial by-products were summarized. Physicochemical properties of incineration industrial by-products were discussed. The effects and hydration mechanism of incinerated ash CLSMs were analyzed. Incineration ash can be used to prepare cementless CLSM. Abstract: Incineration industrial by-products can be used as supplementary cementitious materials (SCMs) to degrade the cement output, thereby reducing fossil-fuel combustion and contributing to the utilization and management of waste resources. This paper summarizes the state-of-the-art uses of incineration industrial by-products (coal ash, waste incineration ash, and biomass incineration ash), which are used as SCMs in partial cement replacement. It also summarizes alkali-activated by-products as cementitious materials that replace all cement with controlled low-strength material (CLSM). After introducing the general situation and physicochemical characteristics of these pozzolanic incineration ashes, the influences and mechanisms of the by-products on the performance of CLSM are summarized and analyzed. The discussions and analyses in this paper are expected to inspire further research and provide a basis for the sustainable development of CLSMs from incineration industrial by-products as cementitious materials.